Predicting cumulative watershed effects in small forested watersheds - Litschert, Sandra E., author; MacDonald, Lee H., advisor (Colorado State University. Libraries, 2009)
Cumulative watershed effects (CWEs), such as the hydrologic and sedimentary changes due to management activities, are a critical concern for many land managers. The goal was to develop a suite of GIS-based models for assessing CWEs in forested watersheds. The models need to be easy-to-use, spatially and temporally explicit, and scientifically based. Delta-Q and FOREST (FORest Erosion Simulation Tools) are a series of empirical and conceptual models that calculate the annual changes in discharge (Delta-Q) and annual sediment production, delivery and yield (FOREST) from roads, fires, and forest management. Given the paucity of data on hillslope sediment delivery, a field study also was conducted to assess the connectivity of sediment pathways from timber harvest units. Delta-Q and FOREST were verified using data from the Eldorado National Forest in California. The models were evaluated using measured data from three experimental watersheds. The predicted and measured 50th percentile flows were closer than the 1st and 99th percentiles, as extreme flows are more sensitive to climatic fluctuations. While predicted bedload sediment yields usually fell within the range of measured values, suspended sediment yields were generally overpredicted. FOREST results were most sensitive to changes in mean annual precipitation and GIS data scale. FOREST generates GIS layers to show the hillslopes, roads, and stream reaches with the greatest risk for altering runoff and erosion, and inducing sedimentation. Both models can be used to compare management scenarios within a watershed or among watersheds. By design the models take a middle approach between commonly used, unvalidated empirical models, and complex physically based models that are rarely used by land managers. During the field study in the Sierra Nevada mountains of California, the downslope edges of nearly 200 timber harvest units were traversed. Only 19 rills or sediment plumes were found that originated from harvest units. Five of the six features that extended through the stream-side management zone to a stream channel were generated by runoff from skid trails. The results indicate that harvest units rarely deliver sediment to streams, but post-harvest skid trail treatments may be needed to reduce surface runoff and sediment delivery to streams.
Keywords: bedload sediment; forested watersheds; surface runoff; watersheds; hydrologic sciences; forestry